Pseudomonas aeruginosa Regulates Flagellin Expression as Part of a Global Response to Airway Fluid from Cystic Fibrosis Patients - Wolfgang, Matthew C.; Jyot, Jeevan; Goodman, Andrew L.; Ramphal, Reuben; Lory, Stephen; Tiedje, James M. (Proceedings of the National Academy of Sciences - PNAS, 2004)
Cystic fibrosis (CF) patients are highly susceptible to chronic lung infections by the environmental bacterium Pseudomonas aeruginosa. The overproduction and accumulation of dehydrated viscous respiratory mucus and excessive inflammation represents a defining feature of CF and constitutes the major environment encountered by P. aeruginosa during chronic infections. We applied whole-genome microarray technology to investigate the ability of P. aeruginosa to respond to signals found in muco-purulent airway liquids collected from chronically infected CF patients. Particularly notable was the activation of the Rhl-dependent quorum-sensing (QS) network and repression of fliC, which encodes flagellin. Activation of the Rhl branch of the QS network supports the observation that QS molecules are produced in the chronically infected CF lung. The shut-off of flagellin synthesis in response to CF airway liquids was rapid and independent of QS and the known regulatory networks controlling the hierarchical expression of flagellar genes. As flagellin is highly immunogenic and subject to detection by host pattern recognition receptors, its repression may represent an adaptive response that allows P. aeruginosa to avoid detection by host defense mechanisms and phagocytosis during the chronic phase of CF lung infections.